2022
DOI: 10.1111/ced.15194
|View full text |Cite
|
Sign up to set email alerts
|

Topical steroid withdrawal through the lens of social media

Abstract: The term ‘topical steroid withdrawal’ (TSW) describes an adverse effect that generally occurs with inappropriate prolonged use of high‐potency topical corticosteroids (TCS). The presence of user‐generated content relating to TSW on social media (SoMe) has not been well‐defined to date. We aimed to explore content relating to topical steroid withdrawal on SoMe. Using a data analytics platform, we retrospectively analysed the hashtag #topicalsteroidwithdrawal on SoMe over a 5‐year period from 8 February 2016 unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Mapping both research evidence and social media evidence is a methodological innovation in the production of EGMs. The inclusion of social media evidence was in recognition of the increased presence of #topicalsteroidwithdrawal on social media [15], and how social media content could contribute to understanding the patient perspective of TSWS. Social media is increasingly used by qualitative health researchers and there has been some interest in social media within the dermatological community [43].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mapping both research evidence and social media evidence is a methodological innovation in the production of EGMs. The inclusion of social media evidence was in recognition of the increased presence of #topicalsteroidwithdrawal on social media [15], and how social media content could contribute to understanding the patient perspective of TSWS. Social media is increasingly used by qualitative health researchers and there has been some interest in social media within the dermatological community [43].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although the MHRA described TSWS as 'rare', it is estimated to occur in approximately 12% of people with atopic dermatitis who use TCSs [4]. Evidence for the increasing awareness of TSWS is demonstrated by the rapid growth in social media posts and discussions on TSWS [3,[15][16] and the introduction of online communities such as ITSAN (International Topical Steroid Awareness Network) and Scratch That, UK. It suggests that people living with TSWS are using social media for information and support, particularly as patients have reported feeling ignored, dismissed or blamed by their doctors for inappropriate use of TCSs [17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Between 2016 and 2021, there was a 274% increase in mentions of TCSW on social media platforms, indicating a growing societal awareness of this condition. 4 Limited high-quality clinical research has hindered the establishment of clear definitions and diagnostic criteria. 5 It has been reported that representative histological features commonly include thinned epidermis and numerous dilated vessels in the dermis, resulting in persistent and stubborn facial erythema, as well as skin barrier dysfunction, accompanied by symptoms such as burning, stinging, itching, and flushing.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found an almost six times increase in discussion of #topicalsteroidwithdrawal on the social media platform Instagram between 2020 and 2016, with >618 354 mentions in a 12-month period. 4 Many sufferers believe that TCSs caused their problem and must be avoided at all costs. Patient support groups 5 are calling for earlier recognition, advocacy and research into TSWS.…”
mentioning
confidence: 99%